Agronomic studies on chickpea (Cicer arietinum L.) - Plancquaert P.; Braun P.; Wery J. (Present status and future prospects of chickpea crop production and improvement in the Mediterranean countries, 1990)
The potential yield of chickpeas is high, particularly when sown early. Farmers have to be advised on proper crop management in order to enable them to attain high yields. With this aim in view experiments were carried out identiying optimun plant population and suitable weed control methods within a network of research in France. The optimum plant population is higher when date of planting is early, variety is compact and when enough water is available. Pre-sowing application of AVADEX is convenient. However, the best control is with pre-emergence application of such herbicides as BOCHAMP, CENT 7, PREMIUM, DINOGRANE SP, TRIBUNIL, ZEPHIR and neburon. Post-emergence herbicides are not so selective.
Present Status and Future Prospects of Chickpea Crop Production and Improvement in the Mediterranean Countries, 11-13 Jul 1988, Zaragoza (Spain)